Alfabetização financeira: integrando conhecimento, atitude e comportamento financeiros - Potrich, Ani Caroline Grigion (2014)
This study had as its objective develop a model to evaluate the level of financial literacy of citizens in the South of Brazil, able to integrate constructs related to financial knowledge, financial attitude and financial behavior. To achieve the objective, a survey with 1.576 inhabitants of the seven mesoregions in Rio Grande do Sul has been done. A questionnaire has been adopted as an instrument to collect data and it is formed by seventy-five questions and approaches socioeconomic and demographic variables and three constructs (financial attitude, financial behavior and financial knowledge). The model estimated by structural equation modeling and sociable and demographic variables influence have been measured by parametric hypothesis tests. Results have shown that from the thirty-seven initial variables for financial attitude and financial behavior constructs, eight have been validated. From the two structural models proposed, the one with the best adjustment and that measured financial literacy better was the second order factorial, where constructs financial attitude, financial knowledge and financial behavior have been maintained separately and financial literacy has turned into a second order construct. The constructs descriptive statists has shown an adequate level of financial attitude and intermediate levels of financial behavior for citizens in Rio Grande do Sul. Hypothesis tests have pointed out to significant differences among the three constructs, where the variable age has not shown any difference among groups. Furthermore, the most relevant aspects to financial literacy are related to concern about the future and saving money monthly.